USAHA MENINGKATAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN SURVEI DAN PEMETAAN KELAS X TEKNIK KONSTRUKSI BANGUNAN (TKB) DI SMK NEGERI 2 SURAKARTA - Pratiknyo, Edy; Sukatiman, Sukatiman; Sutrisno, Sutrisno (Pendidikan Teknik Bangunan, 2015)
Edy Pratiknyo. EFFORT TO INCREAS STUDENT SCORE BY CONTEXTUAL OF LEARNING IN SURVEY AND MAPPING TECHNICAL BUILDING CONSTRUCTION (TKB) ON VOCATIONAL HIGH SCHOOL OF SURAKARTA 2 (SMK N 2). Script, Surakarta : Faculty of Teacher and Education Science Sebelas Maret University, April 2014.The purpose of this research is : (1) To detect available or not the influence of student learning result X grade TKB 2013/2014 Vocational High School 2 of Surakarta. (2) To detect available or not inreasing student active in survey and mapping learning.This Research is a classroom action research that held in two cycles. First cycle begin with identification of problem that happen the class room, planning like arragement learning steps by using a model cooperative learning with   contextual approachment method (Contextual Teaching and Learning) that usually brief (CTL). CTL is study concept that help a teacher to connect between material teaching and situation real. Subject of student of X was grade technic of building construction (TKB) in SMK N 2 Surakarta year teaching 2013/2014. The data whos got from affective observation and cognitive test. Data analysis using technic of descriptive analysis.Research of the result showed that using of learning cooperative by approachment contextual method cane increase score of student learning. (1) By using Contextual Teaching approach student achievement in Survey and Mapping subject could be better than before, now students' grade have been above MPG (Minimum Passing Grade) >= 75 (2) Students activity in Survey and Mapping class have been increased since the use of Contextual Teaching and Learning approach, Student Activity have been raised from 25% up to 80%. Result of student learning cognitive domain (Before Cycle = 60,62% ; Cycle I = 85,20% ; Cycle II = 87,50%). Result of student learning on affective domain (before cycle = 57,36% ; Cycle I = 78,55% ; Cycle II = 88,88%). Cooperative learning model by effective contextual approachment metod to increasi scores of student learning, its visible from learning processed that prevailed.Keywords     : Contextual Learning, Cooperative Model, Cycle Learning, Raising Result of Learning Student.